Desenvolvimento tecnológico de fitoproduto a partir de Justicia pectoralis – chambá : obtenção do extrato seco padronizado (CLAE-DAD) e avaliação farmacológica - Fonseca, Francisco Noé da (2009)
Justicia pectoralis (Acanthaceae), known as “chambá”, is an herb popularly used for the treatment of asthma. This species has been selected for the Phytotherapy Public Programs in Northeast and included in the National Medicinal Plants list of Interest to the Unified Health System. At least a part of the anti-inflammatory and bronchodilatador activities of J. pectoralis has been related to the presence of coumarin (CM) and umbelliferone (UMB), active principles / chemical markers. In order to innovate and aggregate more technology to the phytoproducts from J. pectoralis, the present work aimed to develop the best process to obtain the standardized extract (SEJP) and to investigate its pharmacological properties. It was developed and validated a high performance liquid chromatography method (HPLC – PDA) to determine the concentration of CM and UMB in extract from aerial parts from J. pectoralis. It was established the conditions to produce the drug in a dryer chamber with air circulation and renovation, as well as the pharmacognostic parameters of the product obtained. The influences of the extraction variables related to the extraction method (percolation: maceration time, drug:solvent proportion and alcoholic percentage in water) were evaluated by a factorial planning (2³), on what the drug:solvent proportion and ethanol content affected the amount of CM and UMB in the extracts. The hydroalcoholic extract of “chambá” produced using the selected conditions (drug:solvent proportion 1:15; ethanol content: 20 %; maceration time: 24 h) was characterized physical-chemically and then submitted to spray drying (using colloidal silicon dioxide as adjuvant), being determinated its physical-chemical properties. The toxicological evaluation in vitro of dry extract (CM: 8,84 mg/g; UMB: 1,27 mg/g) showed low citotoxicity to human neutrophils, measured by the lactate dehydrogenase enzyme activity. The standardized extract (SE; 100, 200 and 400 mg/Kg) reduced around 38 % the paw edema induced by carrageenan in mice and also the release of MPO induced by PMA in human neutrophils. On the other hand, it did not interfere in the paw edema induced by dextan. The SE also reduced the nociception induced by capsaicin in mice, causing inhibition of until 79,6 %. In conclusion, the present study supports the development of standardized phytomedicine from J. pectoralis. The pharmacological evaluation of the SE from this plant demonstrated its low citotoxicity in human neutrophil, besides the anti-inflammatory and antinociceptive.